Aspects of Nitric Oxide in Health and Disease: A Focus on Hypertension and Cardiovascular Disease - Giles, Thomas D. (J Clin Hypertens (Greenwich), 2007)
Nitric oxide (nitrogen monoxide) (NO) plays an important role in a wide range of physiologic processes. A major mediator of endothelial function, NO regulates vasodilatory and antithrombotic actions in the vasculature and plays a role in reproductive functions, bronchodilation, bone formation, memory, insulin sensitivity, and gastrointestinal relaxation. NO is formed from NO synthase. Impaired NO bioactivity is strongly associated with endothelial dysfunction and cardiovascular disease, but is also implicated in a broad range of other disorders, including pulmonary hypertension, insulin resistance, erectile dysfunction, and preeclampsia. Numerous therapies designed to target NO are being investigated and developed, including NO donors and stimulants. The recent African‐American Heart Failure Trial (A‐HeFT) showed that the NO donor isosorbide dinitrate, combined with the vasodilator hydralazine, significantly reduced morbidity and mortality in black patients with moderate‐to‐severe heart failure. Antihypertensive drugs, including angiotensin‐converting enzyme inhibitors, calcium channel blockers, and third‐generation β‐blockers, are NO stimulants that have demonstrated significant improvement of endothelial function and NO bioactivity. Other cardiovascular therapies that may improve NO bioactivity include statins, L‐arginine, and hydralazine approaches such as exercise and dietary changes.